Building Higher Order Thinking Skills (Hots) for Pre-Service Vocational Engineering Teachers by Applying a Multi-Method Approach to the Learning Process through Lesson Study. - Rahmawati, Anis; Nurhidayati, Aryanti; Saputro, Ida Nugroho (Pertanika Journal of Social Sciences & Humanities, 2019)
This article aims to examine the implementation of a multi-method approach in the vocational engineering learning process through a Lesson Study to develop higher order thinking skills (HOTS) for pre-service teachers. This is a multiphase mixed methods design which included a series of Lesson Study activities. In the implementation phase, the multi-method learning was started through self-directed learning, followed by collaborative problem-solving by using a mixture of several techniques. The last phase was a summarization session. The results of this study indicate that a multi-method approach has the potential to develop pre-service teachers' HOTS.